2016
DOI: 10.1128/jcm.02047-15
|View full text |Cite
|
Sign up to set email alerts
|

Performance of BD Max StaphSR for Screening of Methicillin-Resistant Staphylococcus aureus Isolates among a Contemporary and Diverse Collection from 146 Institutions Located in Nine U.S. Census Regions: Prevalence of mecA Dropout Mutants

Abstract: This study determined the performance of BD Max StaphSR and the rate of methicillin-resistant Staphylococcus aureus (MRSA) with an unrecognized staphylococcal cassette chromosome mec (SCCmec) right-extremity junction (MREJ) region among 907 methicillin-resistant S. aureus (MRSA) and 900 methicillin-susceptible S. aureus (MSSA) isolates. The rate of mecA/mecC dropout mutants was also evaluated. Only three MRSA isolates (99.7% sensitivity; 904/907) were classified as MSSA by the BD Max StaphSR assay, due to nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…All MRSAXT results generated with MRSA and MSSA were in agreement with those obtained previously by BD Max StaphSR, including the presence of three false-negative and eight false-positive MRSA results (1 These results suggest that the MRSAXT and StaphSR assays provide equivalent results for screening of MRSA while also correctly identifying dropout mutants as MSSA (or MRSA negative). Both systems use the same sets of primers and probes targeting the MREJ region, nuc, and mecA/C.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…All MRSAXT results generated with MRSA and MSSA were in agreement with those obtained previously by BD Max StaphSR, including the presence of three false-negative and eight false-positive MRSA results (1 These results suggest that the MRSAXT and StaphSR assays provide equivalent results for screening of MRSA while also correctly identifying dropout mutants as MSSA (or MRSA negative). Both systems use the same sets of primers and probes targeting the MREJ region, nuc, and mecA/C.…”
supporting
confidence: 78%
“…e recently reported the performance of the BD Max StaphSR assay for screening of methicillin-resistant Staphylococcus aureus (MRSA), as well as the prevalence in the U.S. of S. aureus carrying a staphylococcal cassette chromosome (SCCmec) element lacking mecA (so-called dropout mutant) (1). This assay targets the nuc and mecA/C genes and 11 sequences of the SCCmec-orfX right-extremity junction (MREJ) region.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The MRSA NxG assay evaluated in this study showed similar performance characteristics, with an overall specificity of 97.2%. Previous generations of MRSA molecular assays were prone to false-positive results when tested on strains containing an empty SCCmec cassette (i.e., mecA dropout strains), which are estimated to occur in about 7% of methicillin-susceptible S. aureus (MSSA) isolates in the United States (33). However, this problem was remedied in subsequent assays through the inclusion of primers and probes targeting both the junction of the SCCmec cassette with the orfx gene and the mecA gene.…”
Section: Discussionmentioning
confidence: 99%